The prescription of administrative infractions in Peruvian Punitive Administrative Law - Ayvar Ayvar, Ricardo (2019)
Prescription is a critical legal construct in Peruvian punitive administrative law, since it establishes a limit to the the punitive power of the State, which provides the citizens the legal certainty that they need when engaging with the public administration. Although most administrative procedures are regulated by a general norm, it is also necessary to consider the impact of specific norms on this institution.The author analyzes this topic by, first, addressing the legal status and typology of prescription to further adopt a stance regarding its legal framework. At last, the author refers to the materiality of its exceptional circumstances: the interruption and suspension of the limitation period.